2023
DOI: 10.3390/nano13091554
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catalytic Epoxidation–Hydration of α-Pinene with Hydrogen Peroxide to Sobrerol by Durable Ammonium Phosphotungstate Immobilized on Imidazolized Activated Carbon

Abstract: It is presented that the activated carbon was carboxylated with hydrogen peroxide and then acylated with 2-methylimidazole to prepare the porous carbon support with a surface imidazolated modification. Through the adsorption of phosphotungstic acid on the fundamental site of an imidazolyl group and then adjusting the acid strength with the ammonia molecule, a catalytic carbon material immobilized with ammonium phosphotungstate (AC-COIMO-NH4PW) was obtained, which was used to catalyze a one-pot reaction of conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The FTIR spectrum and XRD of activated carbon (AC), phosphotungstic acid supported on imidazolized AC (AC-COIMI-HPW), and ammonium phosphotungstate anchored by imidazolized AC (AC-COIMI-NH4PW) is shown in Figure 1A. The FTIR spectrum of AC in Figure 1A showed that the absorption peaks at 1608 cm −1 and 1400 cm −1 attributed to C=C stretching vibration of the cyclic aromatic skeleton in AC, and there is the characteristic absorption peak of -OH linked at the edge of fused polycyclic aromatic in the bulk of AC at 3130cm In our previous work, it was found that imidazolated nitrogenated activated carbon anchoring phosphotungstate had excellent catalytic performance for benzyl alcohol [24], and the reaction of α-pinene with hydrogen peroxide on ammonium phosphotungstate immobilized on imidazolated nitrogenated activated carbon could selectively convert to sobrerol [25]. In present work, ammonium phosphotungstate anchored by imidazolated nitrogenous activated carbon was developed to catalyze α-epoxypinane ring-opening rearrangement, so as to improve the selective synthesis of carveol and provide a new green [26] catalytic material system from biomass based activated carbon for the preparation of high-value carveol from plentiful and cheap turpentine.…”
Section: Structure and Texture Characteristics Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FTIR spectrum and XRD of activated carbon (AC), phosphotungstic acid supported on imidazolized AC (AC-COIMI-HPW), and ammonium phosphotungstate anchored by imidazolized AC (AC-COIMI-NH4PW) is shown in Figure 1A. The FTIR spectrum of AC in Figure 1A showed that the absorption peaks at 1608 cm −1 and 1400 cm −1 attributed to C=C stretching vibration of the cyclic aromatic skeleton in AC, and there is the characteristic absorption peak of -OH linked at the edge of fused polycyclic aromatic in the bulk of AC at 3130cm In our previous work, it was found that imidazolated nitrogenated activated carbon anchoring phosphotungstate had excellent catalytic performance for benzyl alcohol [24], and the reaction of α-pinene with hydrogen peroxide on ammonium phosphotungstate immobilized on imidazolated nitrogenated activated carbon could selectively convert to sobrerol [25]. In present work, ammonium phosphotungstate anchored by imidazolated nitrogenous activated carbon was developed to catalyze α-epoxypinane ring-opening rearrangement, so as to improve the selective synthesis of carveol and provide a new green [26] catalytic material system from biomass based activated carbon for the preparation of high-value carveol from plentiful and cheap turpentine.…”
Section: Structure and Texture Characteristics Of Catalystsmentioning
confidence: 99%
“…In our previous work, it was found that imidazolated nitrogenated activated carbon anchoring phosphotungstate had excellent catalytic performance for benzyl alcohol [24], and the reaction of α-pinene with hydrogen peroxide on ammonium phosphotungstate immobilized on imidazolated nitrogenated activated carbon could selectively convert to sobrerol [25]. In present work, ammonium phosphotungstate anchored by imidazolated nitrogenous activated carbon was developed to catalyze α-epoxypinane ring-opening rearrangement, so as to improve the selective synthesis of carveol and provide a new green [26] catalytic material system from biomass based activated carbon for the preparation of high-value carveol from plentiful and cheap turpentine.…”
Section: Introductionmentioning
confidence: 99%